Characterization and genome organization of a repetitive element associated with the nucleolus organizer region in leporinuselongatus (anostomidae: Characiformes) - Da Silva, E. L. [UNESP]; Busso, A. F. [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Karger Publishers, 2012)
Chromosome mapping and studies of the genomic organization of repetitive DNA sequences provide valuable insights that enhance our evolutionary and structural understanding of these sequences, as well as identifying chromosomal rearrangements and sex determination. This study investigated the occurrence and organization of repetitive DNA sequences in Leporinus elongatus using restriction enzyme digestion and the mapping of sequences by chromosomal fluorescence in situ hybridization (FISH). A 378-bp fragment with a 54.2% GC content was isolated after digestion with the SmaI restriction enzyme. BLASTN search found no similarity with previously described sequences, so this repetitive sequence was named LeSmaI. FISH experiments were conducted using L. elongatus and other Anostomidae species, i.e. L. macrocephalus,L. obtusidens, L. striatus, L. lacustris, L. friderici, Schizodon borellii, S. isognathus, and Abramites hypselonotus which detected signals that were unique to male and female L. elongatus individuals. Double-FISH using LeSmaI and 18S rDNA showed that LeSmaI was located in a nucleolus organizer region (NOR) in the male and female metaphases of L. elongatus. This report also discusses the role of repetitive DNA associated with NORs in the diversification of Anostomidae species karyotypes. Copyright © 2012 S. Karger AG, Basel.
Keywords: FISH; LeSmaI; Neotropical fish; NOR; Repetitive DNA; DNA 18S; genomic DNA; repetitive DNA; restriction endonuclease; ribosome DNA; silver nitrate; animal experiment; animal tissue; Characiformes; chromosome map; chromosome NOR; chromosome preparation; cistron; diploidy; DNA base composition; female; fluorescence in situ hybridization; genome analysis; karyotype; male; metaphase; nonhuman; priority journal; restriction fragment; sex chromosome; Animals; Base Sequence; Blotting, Southern; Chromosome Mapping; Female; Genome; In Situ Hybridization, Fluorescence; Male; Molecular Sequence Data; Nucleolus Organizer Region; Repetitive Sequences, Nucleic Acid; RNA, Ribosomal, 18S; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Abramites hypselonotus; Anostomidae; Leporinus elongatus; Schizodon borellii